THE IMPACT OF DIGITAL MONEY TURNOVER VELOCITY ON THE INDONESIAN ECONOMY - Abdul Mukhyi, Mohammad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study investigates the impact of digital money turnover velocity on the Indonesian economy, focusing on economic growth, inflation dynamics, employment, and financial inclusion. The primary objective is to understand how the rapid circulation of digital money influences key economic indicators and contributes to poverty reduction. Utilizing a qualitative research methodology, this study conducts a comprehensive literature review and employs a meta-analysis of existing empirical studies to synthesize findings related to digital money and economic performance. The analysis reveals that an increase in the velocity of digital money significantly enhances economic growth by improving transaction efficiency and stimulating consumption. However, it also presents potential challenges, such as contributing to inflationary pressures if not managed properly. The study also examines the labor market, highlighting that digital money facilitates job creation in fintech and digital services sectors while promoting financial inclusion by providing access to financial services for previously underserved populations. Furthermore, the findings underscore the critical role of financial literacy in maximizing the benefits of digital money. Enhanced financial literacy ensures that individuals can effectively manage and utilize digital financial services, leading to better financial outcomes and economic empowerment. The research suggests that policy interventions aimed at promoting digital financial services, coupled with comprehensive financial literacy programs, can significantly contribute to economic development and poverty reduction in Indonesia.